2015
DOI: 10.5489/cuaj.2801
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function after surgical treatment for penile cancer: Which organ-sparing approach gives the best results?

Abstract: E423Cite as: Can Urol Assoc J 2015;9(7-8):E423-7. http://dx.doi.org/10.5489/cuaj.2801 Published online July 17, 2015. AbstractIntroduction: We compared the postoperative sexual function of patients who underwent wide local excision (WLE) and glansectomy with urethral glanduloplasty for penile cancer. Methods: We retrospectively reviewed clinical data of 41 patients affected by superficial, localized penile cancer (≤cT2a) between 2006 and 2013. Patients with severe erectile dysfunction and not interested in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
(37 reference statements)
1
35
0
Order By: Relevance
“…Though psychosexual adjustment problems were reported by the patients in these studies (ranging from 6 to 35 %), no such problems were reported by our patients [5,[10][11][12]. Kieffer JM et al [14] and Sedigh O et al [13] have studied the effect of partial penectomy on sexual function in patients with carcinoma penis. They have reported very little impact of surgery on sexual desire, interest as well as arousal.…”
Section: Discussionmentioning
confidence: 65%
“…Though psychosexual adjustment problems were reported by the patients in these studies (ranging from 6 to 35 %), no such problems were reported by our patients [5,[10][11][12]. Kieffer JM et al [14] and Sedigh O et al [13] have studied the effect of partial penectomy on sexual function in patients with carcinoma penis. They have reported very little impact of surgery on sexual desire, interest as well as arousal.…”
Section: Discussionmentioning
confidence: 65%
“…Various studies evaluating sexual and urinary dysfunction after penile-preserving surgery using different questionnaires (e.g. International Index of Erectile Function questionnaire; IIEF) [28] confirmed excellent overall urinary function and quality of life [16,26,29]. Patients with (partial) penectomy reported more sexual and urinary problems than those treated with OSS [23,30].…”
Section: Discussionmentioning
confidence: 99%
“…Total glansectomy first described by Austoni in 1996 [40] is indicated in lesions which are localized but are not amenable to partial glansectomy or are T2 lesions. If the tumor invades tunica albuginea and/or corpora cavernosa, then total glansectomy was performed followed by either splitthickness skin graft reconstruction or reconstruction of cavernosal tips and grafting, if a distal corporectomy was required.…”
Section: Glansectomymentioning
confidence: 99%
“…Omid Sedigh et al looked into the sexual function after surgical treatment for penile cancer and found that wide local excision lead to better sexual outcomes and less postoperative complications as compared to glansectomy with urethral glanduloplasty hence when feasible; wide local excision could represent the best conservative approach to treat localized primary penile cancer [40].…”
Section: Wide Local Excisionmentioning
confidence: 99%